2005
DOI: 10.1111/j.1464-410x.2005.05679.x
|View full text |Cite
|
Sign up to set email alerts
|

Local steroid application during nerve‐sparing radical retropubic prostatectomy

Abstract: potency were evaluated at 3, 6 and 12 months in all patients and compared between the groups. RESULTSAt 12 months, 57% and 60% of patients were potent in group 1 and 2, respectively; the respective mean International Index of Erectile Function (5-item) scores were 14.76 and 15.43 ( P = 0.59). Potency rates at 3, 6 and 12 months were not significantly different between the groups, and the continence rates at 12 months were also similar, with 93% and 90% of patients in groups 1 and 2 being continent, respectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Initial search of the PubMED/MEDLINE and EMBASE databases retrieved 1,326 publications, 796 from the PubMED/MEDLINE database and 1,156 from the EMBASE database. Initial exclusion of publications reporting on a study group of less than 50 subjects and/or presenting EF data collected after less than 12‐month follow‐up after RP yielded 212 publications, eligible for further full review and 22 studies (10%) met full inclusion criteria (Figures 1 and 2) [12–33]. Of the 9,965 total subjects, appropriate ED data were available for 4,983.…”
Section: Resultsmentioning
confidence: 99%
“…Initial search of the PubMED/MEDLINE and EMBASE databases retrieved 1,326 publications, 796 from the PubMED/MEDLINE database and 1,156 from the EMBASE database. Initial exclusion of publications reporting on a study group of less than 50 subjects and/or presenting EF data collected after less than 12‐month follow‐up after RP yielded 212 publications, eligible for further full review and 22 studies (10%) met full inclusion criteria (Figures 1 and 2) [12–33]. Of the 9,965 total subjects, appropriate ED data were available for 4,983.…”
Section: Resultsmentioning
confidence: 99%
“…The anatomical techniques used in RRP results in decreased blood loss and thus better visualization and safer dissection of the neurovascular bundles [2,3]. Many studies on erectile dysfunction (ED) following nerve-sparing RRP have been published, revealing widely disparate potency rates (30-86%) among various groups in different studies [4][5][6][7][8][9][10][11]. This variation in potency rates may be due to patient selection, surgeon and hospital volume, and the proportion of nerve-sparing procedures [5,[12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…The medication was started 16-22 h after surgery. A similar study was done with the intraoperative local administration of betamethasone cream 0.1% on the area of the CN in 60 men [49]. Neither study demonstrated appreciable improvement in erection recovery after 12 months follow-up.…”
Section: Corticosteroidsmentioning
confidence: 87%